THE INTERACTION BETWEEN SUBSYSTEMS OF FLEXIBLE ASYNCHRONOUS THREAD REPAIR CARS, FORMALIZED IN THE FORM OF AGGREGATIVE SYSTEM - Myamlin, V. V. (Science and Transport Progress, 2009)
Negative aspects of traditional production-and-conveyer lines for wagon repair are shown. Advantages of a new type of wagon-repair flow – asynchronous flexible one – are considered. An aggregative system is suggested as a mathematical model of functioning of the asynchronous flexible flow. Peculiarities of interaction between aggregative subsystems are demonstrated.